Three-dimensional wafer stacking using Cu–Cu bonding for simultaneous formation of electrical, mechanical, and hermetic bonds - Tan, Chuan Seng (2013)
Wafer-on-wafer stacking is demonstrated successfully using bumpless Cu-Cu bonding for the simultaneous formation of electrical connection, mechanical support, and hermetic frame for 3-D IC application. The ohmic behavior of the Cu-Cu bond is verified. A daisy chain of at least 44 000 contacts at a 15-μm pitch is connected successfully and sustains thermal cycling. Postbonding delamination is found to be strongly affected by the wafer curvature and bond strength. The Cu-Cu hermetic seal ring shows a helium leak rate more than ten times lower than the reject limit (5 × 10-8 atm · cm/s based on MIL-STD-883E standard) without underfill. This provides a robust IC-to-IC connection density of 4.4 × 105 cm-2, suitable for future wafer-level 3-D integration.